Exotic Dramatic Fashion Inspired by the Form of Mosque Domes - Sartika; Mirda Aryadi; Dini Yanuarni; Novina Yeni Fatrina (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The final project entitled “Exotic Dramatic Style by Applying the Shape of a Mosque Dome” presents a fashion collection inspired by the architectural form of a mosque dome in an exotic dramatic style. This style emphasizes unique, ethnic, and dramatic characteristics through a strong visual appearance using maroon, black, and gold. The dome design is inspired by the areca nut-shaped dome of the Terapung Samudera Ilahi Mosque in Painan. The collection consists of ready-to-wear, ready-to-wear deluxe, and haute couture garments made from bridal satin, silk taffeta, Yamaha satin, and lurik woven fabric. Decorative tassel embroidery, created from circular fabric pieces shaped into cones and combined with beads, emphasizes the three-dimensional dome form while enhancing the garments' aesthetic value. The creative process included field exploration, literature studies, and design development based on the Loud Luxury and Regenerative Craft trends (2025/2026). The final collection comprises Kubahana, Dome of Majesty, and The Golden Arch. Keywords: Exotic dramatic style, mosque dome, fashion design.